Social Relations and the Meaning of Online Loan Applications (A Phenomenological Study in RT 05, Kelapa Tiga Permai Subdistrict, Bandar Lampung City) - Taufik Farhansyah; Noning Verawati; Budhi Waskito (Universitas Dharmawangsa Medan, 2025)
This research explores the interpersonal communication experiences and social relationships formed through the use of online loan applications among residents of RT 05 Kelurahan Kelapa Tiga Permai, Bandar Lampung. The rapid growth of digital lending platforms, particularly in Lampung, has created new financial behaviors and communication patterns among users, especially in economically pressured communities. This study employs a qualitative method with a phenomenological approach to deeply understand how borrowers interpret and experience their interactions before, during, and after using online loans. Data were collected through in-depth interviews, observations, and documentation from selected informants, including key community figures, active borrowers, and individuals impacted by these financial practices. The findings reveal that online loans are not solely understood as financial tools but also as social phenomena embedded in daily interpersonal interactions. Social relationships play a critical role in shaping perceptions, building trust, and spreading both accurate and misleading information regarding the use of online loans. Peer influence, emotional support, and communal narratives significantly contribute to the decision-making process. Moreover, experiences shared among neighbors and family members often determine how the service is perceived either as a convenient solution or a trap with long-term consequences. The study concludes that online loan experiences are shaped not only by economic needs but also by cultural communication practices that construct meaning and influence behavior in a digitally connected society.